Optimization of anticancer exopolysaccharide production from probiotic Lactobacillus acidophilus by response surface methodology. Issue 3 (2nd April 2016) - Deepak, Venkataraman; Ram Kumar Pandian, Sureshbabu; Sivasubramaniam, Shiva D.; Nellaiah, Hariharan; Sundar, Krishnan
ABSTRACT: Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths in the Western world. Recently, much attention has been focused on decreasing the risk of CRC by consuming probiotics. In the present study, exopolysaccharide (EPS) extracted from Lactobacillus acidophilus was found to inhibit the growth of CaCo2 colon cancer cell line in a dose-dependent manner. The experiment was performed in both normoxic and hypoxic conditions, and EPS was found to reduce the survival of CaCo2 cell line in both the conditions. Quantitative polymerase chain reaction (qPCR) studies demonstrated that EPS treatment upregulated the expression of peroxisome proliferator activator receptor-γ (PPAR-γ) in both normoxia and hypoxia conditions, whereas it upregulated the expression of erythropoietin (EPO) in the normoxic condition, but there was no significant expression under hypoxic conditions. Hence, the EPS production was optimized by Plackett–Burman design followed by central composite rotatory design. The optimized production of EPS at 24 hr was found to be 400 mg/L. During batch cultivation the production peaked at 21 hr, resulting in an EPS concentration of 597 mg/L.